High Intensity Tabata Bodyweight Training Increasing Maximum Oxygen Volume in Students - Gigih Siantoro; Bayu Agung Pramono; Frista Anggraini; Muhammad Arodista; Musa Bagaskara; Eky Ramadhani; Tanaka Pahlevi; Sheylla Putri; Errik Firmansyah; Rifqy Sulthoni (UNIB Press, 2024)
Tabata workouts are exercises that use intensity with monotonous and numerous movements​ that pile up an injury. In the research, this researcher modified exercise tabata using bodyweight training to motivate students when they exercise with the Tabata model. Besides, modification intensity supports students who are spared from frequent injuries​, especially athletes who exercise tabata with intensity. Research purposes This is for known influence exercise tabata to increase students' VO2Max with modification movement and intensity that has been modified. The type of research used is a study experiment with design one group pretest-posttest design research. 11 students will participate in a study; they will do exercise tabata with an intensity of 80-90% 3 times a week for 3 weeks. The entire subject involved in the study is active students​ who do physical activity at least 2 times a week. The paired sample t-test was used in the study. The research result is that there is a difference between pre and post-surgery students who exercise tabata for 3 weeks (p ≤ 0.05) with an increase in VO2Max by 15.93%. Conclusions study This exercise tabata for 3 weeks is capable of increasing VO2Max in students. Modified Tabata workout​ with bodyweight training movements with 8 different movements gives significant enhancement to students' VO2Max.